Research on the positioning and enhancement path of marine cities in China’s internal circulation network - Sun, Junkai; Gao, Xinyue; Zhang, Xindan; Dai, Guilin (Frontiers in Marine Science, 2024)
China's marine cities have reached a critical juncture after 40 years of rapid development. In this new stage, where internal circulation is the main focus, there is a need to enhance the internal circulation capabilities of these cities and unleash their full economic potential. Based on data from 284 prefecture-level cities in China, this paper constructs the social network of China's urban internal circulation with the help of the modified gravity model, and explores the conditional configuration of the improvement of the status of marine cities in internal circulation network by using the fuzzy-set qualitative comparative analysis (fsQCA) method. The key findings include: (1) The development level of marine cities' internal circulation can be categorized into three tiers, led by Shanghai. The development gap between the 14 marine cities has gradually widened over recent years. (2) Chinese marine cities can be divided into three groups in the topological structure of China's urban internal circulation network: core, periphery, and edge, with Shanghai being the core "bridge" in the network. The traditional advantages of some northern economically strong cities in the construction of the internal circulation network have gradually been lost, and many marine cities have seen their leadership and control over the internal circulation network significantly weakened.(3) No single factor is a necessary condition for achieving a high-level status of marine cities in the internal circulation network. (4) The four conditional variables of demand side, supply side, industrial linkage and inter-regional integration have two sufficient condition configurations to enhance the status of marine cities in internal circulation network. Among them, the "industryregional integration" -dominated configuration with the core of unblocking the bottlenecks of the internal circulation is the main path.